ANALYSIS OF THE MECHANISMS OF FINANCIAL SUPPORT OF ENTERPRISES (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In the article, the problems of improving the theory and methodology of forming the financial policy of the enterprise at the current stage of economic liberalization and modernization in the Republic of Uzbekistan are studied. The advantages and specific features of improving the theory and methodology of the formation of the financial policy of the enterprise in the prospects of the socio-economic development of the country are scientifically substantiated. Possibilities of improving the theory and methodology of the formation of the company's financial policy in the corporate financial management system of the Republic of Uzbekistan were studied and recommendations were developed.